High-strength high-toughness corrosion-resistant maraging stainless steel and preparation method thereof
By adding Al, Nb and Cu elements to martensite aging hardened stainless steel, nano-sized precipitation phases and clusters are formed, combined with a specific heat treatment process, the strength, plasticity and corrosion resistance of martensite precipitation hardened stainless steel is solved. Inadequately, a new martensite aging stainless steel with high strength, high toughness and corrosion resistance has been achieved.
Patent Information
- Application Number
- CN202410012617.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-03
- Filing Date
- 2024-01-04
- Publication Date
- 2024-12-13
AI Technical Summary
The existing martensite precipitated hardened stainless steel has shortcomings in strength, plasticity and toughness, and has low corrosion resistance, which limits its high-speed and high-precision applications in corrosion-resistant conditions.
By reducing the Ti content in martensite aging hardened stainless steel, Al, Nb and Cu elements are added to form nano-sized Ni3Ti, Ni3Nb and Ni3Al precipitation phases and nanoclusters Cu and Mo, combined with small deformation rolling and deep cooling treatment process, A structure consisting of fine slats and sheet-like residual austenite is formed, and a low-temperature long-term aging heat treatment is used to form high-density nano-sized precipitation phases to improve corrosion resistance and strengthening effect.
It achieves high yield strength and tensile strength exceeding 1800MPa and 1900MPa, hardness exceeding 52HRC, elongation and cross-section shrinkage exceeding 20% and 50%, impact and fracture toughness exceeding 50J/cm2 and 120MPa·m1/2, significantly improving stainless steel High strength and high toughness and corrosion resistance, while reducing costs.
Smart Images

Figure CN119121075A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to a high-strength, high-toughness, corrosion-resistant martensitic aged stainless steel and a preparation method thereof. Background Art
[0002] High-strength stainless steel is widely used in aviation, aerospace, marine, nuclear industry and other fields, among which martensitic high-strength stainless steel is the most widely used. Martensitic high-strength stainless steel is divided into aging stainless steel and precipitation hardening stainless steel, which mainly uses martensitic phase transformation strengthening and second phase strengthening to achieve high strength. Among them, martensitic precipitation hardening stainless steel mainly uses Cr 23 Carbide precipitation phases such as C6 serve as strengthening and hardening phases, but Cr 23 The formation of carbides such as C6 will reduce the Cr equivalent in the matrix, thereby reducing corrosion resistance, and the increase in the number of carbides often greatly reduces plastic toughness. At the same time, although precipitation hardened stainless steel is corrosion resistant and has a tensile strength of more than 1800MPa, its yield strength is less than 1400MPa. The huge gap between yield strength and tensile strength limits the application of this type of steel. Martensitic age-hardening stainless steel uses the superposition of carbon-free martensitic phase transformation strengthening and intermetallic compound aging strengthening. On the one hand, ultra-low carbon and high Ni ensure the plasticity of the martensitic matrix. On the other hand, by adding elements such as Co, Mo, and Ti to form intermetallic compounds, excellent aging strengthening effects are achieved, making the stainless steel have higher strength, hardness, toughness and higher corrosion resistance. However, the steel is not strong enough and contains a large amount of expensive alloying elements such as Co, which restricts the application of martensitic ageing steel.
[0003] In the face of the development requirements of high-speed and high-precision components under corrosion-resistant conditions, stainless steel is required to have higher strength and hardness while also having higher plasticity and toughness. Although martensitic age-hardening stainless steel uses intermetallic compound precipitation phases such as Ni3Ti as strengthening phases, it can effectively improve the strength and hardness while effectively improving the corrosion resistance of stainless steel, and has good notch strength, impact toughness and fracture toughness, and can withstand greater torque, it has a wide range of applications in the medical device industry. However, its strength is still significantly lower than that of martensitic precipitation-hardening stainless steel, and its toughness and corrosion resistance are still relatively low. For example, the tensile strength of Custom465 steel is 1700MPa, and the fracture toughness is 80MPa·m 1 / 2 Therefore, the yield strength and tensile strength of martensitic age-hardening stainless steel are more than 1800MPa and 1900MPa respectively, the hardness is more than 52HRC, the elongation and cross-sectional shrinkage are more than 20% and 50%, and the impact and fracture toughness are increased by more than 60J / cm 2 、120MPa·m 1 / 2 , and obtain high corrosion resistance, thus having higher application potential. Summary of the invention
[0004] The present invention aims to solve the problems of strength, plasticity and toughness of the existing martensitic precipitation hardening stainless steel without Co alloy element, and provides a low-cost stainless steel with yield strength and tensile strength exceeding 1800MPa and 1900MPa respectively, hardness exceeding 52HRC, elongation and cross-sectional shrinkage exceeding 20% and 50%, and impact and fracture toughness exceeding 50J / cm 2 、120MPa·m 1 / 2 High-strength, high-toughness and corrosion-resistant maraging stainless steel and a preparation method thereof.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] The high-strength, high-toughness, corrosion-resistant martensitic aging stainless steel of the present invention has the following chemical components by mass percentage: Cr: 11.0%-13.5%, Ni: 9.5%-10.5%, Mo: 0.5%-2.0%, Al: 0.2%-1%, Ti: 0.5%-1.0%, Nb: 0.2%-1.0%, Cu: 0.1%-1.0%, Mn: ≤0.20%, P: ≤0.01%, S: ≤0.01%, Si: ≤0.20%, O: ≤0.01%, C: ≤0.02%, and the balance is Fe.
[0007] The microstructure of the high-strength, high-toughness, corrosion-resistant martensitic aged stainless steel is a matrix composed of fine lath martensite, 5%-10% lamellar residual austenite and film-like reversed austenite, and high-density nano-sized Ni3Ti, Ni3Al, Ni3Nb precipitation phases and Cu and Mo clusters are dispersed on the matrix.
[0008] A method for preparing high-strength, high-toughness, corrosion-resistant martensitic aging stainless steel comprises the following steps:
[0009] Step 1, pure Fe, pure Ni, pure copper, ferrochrome, ferromolybdenum, ferroniobium, and titanium-aluminum alloy are selected and mixed, and then filled into a crucible of a vacuum induction furnace, and heated until completely melted for casting; then the ingot is remelted by vacuum consumable melting or vacuum electroslag remelting before casting;
[0010] Step 2, the ingot is kept at 1100℃~1200℃ for 5h-10h for homogenization treatment and then forged, the forging ratio is 5-9, and the final forging temperature is 850℃~950℃; after forging, it is kept at 850℃~950℃ for 1~2h and then cooled to 400~500℃ and taken out of the furnace. After being taken out of the furnace, the ingot is asbestos coated or buried in sand for slow cooling;
[0011] Step 3, the forging is kept at 850°C to 1000°C, then quickly heated to 1050°C to 1150°C, kept for 0.5h to 2h, and then oil-cooled, and then rolled at 20°C to 300°C by 5% to 15%, with a single-pass reduction rate of ≤5%;
[0012] Step 4, the rolled piece is kept at -80°C to -196°C for 2h-4h and then restored to room temperature, and finally kept at 350°C to 500°C for 6h-18h and then air-cooled, and aged for 2-3 times to obtain high-strength, high-toughness, corrosion-resistant martensitic aged stainless steel.
[0013] The present invention reduces the content of Ti, a main strengthening element, on the basis of Custom465 steel and adds Al, Nb and Cu elements, thereby forming an alloy system in which nano-sized Ni3Ti, Ni3Nb and Ni3Al precipitation phases and nano-clusters Cu and Mo are jointly strengthened, and at the same time, the pitting potential is increased to improve the corrosion resistance of the stainless steel.
[0014] Advantages of the present invention:
[0015] (1) The high-strength, high-toughness, corrosion-resistant martensitic aged stainless steel and its preparation method of the present invention, without adding Co element, by adding multiple alloy elements such as Ti, Al, Nb, Cu, Mo, etc. On the one hand, Cu and Mo elements are used to increase the pitting potential to improve the corrosion resistance of stainless steel; on the other hand, a synergistically strengthened precipitation phase system composed of nano-sized Ni3Ti, Ni3Nb and Ni3Al precipitation phases and nano-clusters of Cu and Mo is formed by heat treatment.
[0016] (2) The high-strength, high-toughness, corrosion-resistant martensitic aged stainless steel and its preparation method of the present invention proposes to combine small deformation rolling and deep cryogenic treatment process to obtain a structure composed of lath martensite and lamellar residual austenite (volume fraction accounts for 5%-10%) uniformly distributed between the lath martensite; and use a low-temperature long-time aging heat treatment process to ensure the formation of reverse austenite while allowing nanoclusters and intermetallic compounds to be dispersed and precipitated in large quantities on the austenite and martensite matrix, ensuring sufficient precipitation strengthening effect, while also avoiding the rapid coarsening of the precipitated phase during the aging process, resulting in a decrease in plasticity and toughness, thereby preparing a new martensitic aged stainless steel with excellent performance.
[0017] (3) The high-strength, high-toughness, corrosion-resistant martensitic aging stainless steel and its preparation method of the present invention provide a high-strength, high-toughness, martensitic precipitation hardening stainless steel with a yield strength and tensile strength exceeding 1800MPa and 1900MPa respectively, a hardness exceeding 52HRC, an elongation exceeding 20%, a cross-sectional shrinkage exceeding 50%, and an impact toughness exceeding 60J / cm 2 , showing obvious high strength and toughness, and the pitting potential exceeds 0.2V SCE ;
[0018] (4) The high-strength, high-toughness, corrosion-resistant martensitic aged stainless steel and its preparation method of the present invention do not contain expensive metals such as Co, and have low Mo and Ti contents, which reduces costs while being compatible with high toughness, high hardness and high corrosion resistance. Compared with conventional high-strength stainless steels such as Custom465, PH13-8Mo, PH17-4, and PH15-5, it has better comprehensive properties in terms of strength, hardness, plasticity, toughness, and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the fracture morphology of the final heat-treated sample of component C in Example 1 of the present invention.
[0020] Figure 2 The microstructure and microscopic features of the martensite matrix of the sample subjected to -130°C cryogenic treatment after aging in Example 2 of the present invention. DETAILED DESCRIPTION
[0021] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings.
[0022] like Figure 1 , 2 As shown, the high-strength, high-toughness, corrosion-resistant martensitic aging stainless steel of the present invention is characterized in that the chemical composition mass percentage of the high-strength, high-toughness, corrosion-resistant martensitic aging stainless steel is: Cr: 11.0%-13.5%, Ni: 9.5%-10.5%, Mo: 0.5%-2.0%, Al: 0.2%-1%, Ti: 0.5%-1.0%, Nb: 0.2%-1.0%, Cu: 0.1%-1.0%, Mn: ≤0.20%, P: ≤0.01%, S: ≤0.01%, Si: ≤0.20%, O: ≤0.01%, C: ≤0.02%, and the balance is Fe.
[0023] The microstructure of the high-strength, high-toughness, corrosion-resistant martensitic aged stainless steel is a matrix composed of fine lath martensite, 5%-10% lamellar residual austenite and film-like reversed austenite, and high-density nano-sized Ni3Ti, Ni3Al, Ni3Nb precipitation phases and Cu and Mo clusters are dispersed on the matrix.
[0024] A method for preparing high-strength, high-toughness, corrosion-resistant martensitic aged stainless steel, characterized by comprising the following steps:
[0025] Step 1, pure Fe, pure Ni, pure copper, ferrochrome, ferromolybdenum, ferroniobium, and titanium-aluminum alloy are selected and mixed, and then filled into a crucible of a vacuum induction furnace, and heated until completely melted for casting; then the ingot is remelted by vacuum consumable melting or vacuum electroslag remelting before casting;
[0026] Step 2, the ingot is kept at 1100℃~1200℃ for 5h-10h for homogenization treatment and then forged, the forging ratio is 5-9, and the final forging temperature is 850℃~950℃; after forging, it is kept at 850℃~950℃ for 1~2h and then cooled to 400~500℃ and taken out of the furnace. After being taken out of the furnace, the ingot is asbestos coated or buried in sand for slow cooling;
[0027] Step 3, the forging is kept at 850°C to 1000°C, then quickly heated to 1050°C to 1150°C, kept for 0.5h to 2h, and then oil-cooled, and then rolled at 20°C to 300°C by 5% to 15%, with a single-pass reduction rate of ≤5%;
[0028] Step 4, the rolled piece is kept at -80°C to -196°C for 2h-4h and then restored to room temperature, and finally kept at 350°C to 500°C for 6h-18h and then air-cooled, and aged for 2-3 times to obtain high-strength, high-toughness, corrosion-resistant martensitic aged stainless steel.
[0029] The metallographic samples under various heat treatment systems of the present invention are ground and polished, corroded by potassium permanganate sulfuric acid solution, and the grain size is observed by ZEISS-40MAT metallographic microscope. The mixed solution of picric acid + hydrochloric acid + alcohol is used for corrosion, and the grain structure is observed by ZEISS-40MAT metallographic microscope.
[0030] In the mechanical properties test, the tensile specimen is a GB / T228-2002 standard specimen, the gauge length of the tensile specimen is 25mm, and the diameter is 5mm. The hardness of stainless steel after heat treatment is tested with a Rockwell hardness tester. The specimen is finely ground after rough grinding to make the upper and lower surfaces parallel and the roughness higher than 0.8. At least three points are measured for each specimen and the average value is taken. The impact sample adopts the national standard GB / T229-1994, the size of the U-mouth specimen is 10mm×10mm×55mm, and the average value of three tests is taken as the average value of impact toughness. The corrosion resistance test is carried out using a CHI660E electrochemical workstation. The experimental solution is 0.1MNa2SO4+xNaCl (PH=3), and the experimental temperature is room temperature 25℃. A three-electrode system is used for electrochemical experiments, with stainless steel as the working electrode, Pt sheet as the auxiliary electrode, and saturated calomel electrode (SCE) as the reference electrode. Potentiodynamic polarization test, scanning rate is 0.5mV / S, scanning potential range is -0.3V (vs. open circuit potential E OC )~1.5V(vs.reference electrode potential E R ), stop the test after the current changes steadily, and take the average value after measuring 3 times.
[0031] Embodiment 1.
[0032] A 25kg steel ingot was melted in a vacuum induction furnace, and the steel composition was set according to Table 1. Pure Fe, pure Ni, pure copper, ferrochrome, ferromolybdenum, ferroniobium, titanium aluminum alloy, etc. were mixed and filled into a crucible, heated until completely melted and cast; the ingot was cast after vacuum consumable remelting; the billet was kept at 1200℃ for 5h for homogenization; then forged, the forging ratio was 9, and the final forging temperature was 950℃; the forging was kept at 950℃ for 1h and then cooled to 400℃ and taken out of the furnace, buried in sand and slowly cooled. After pickling, the forging was heated to 1000℃ with the furnace and kept for 1h, then quickly heated to 1150℃ and kept for 0.5h, then oil-cooled, and cold rolled four times at 20℃, with a total reduction of 5%; then kept at -196℃ for 2h and returned to room temperature, and finally kept at 350℃ for 8h and air-cooled, and aged three times. The final properties are shown in Table 2. Figure 1 This is the fracture morphology of the final heat-treated sample of component C in Example 1.
[0033] Table 1. List of chemical compositions of stainless steel according to the present invention.
[0034] Element C Cr Ni Mo Ti Al Nb Cu Fe A 0.015 11.5 9.50 0.58 1.50 0.50 0.42 0.34 margin B 0.016 11.0 9.97 1.55 0.50 0.87 0.20 0.56 margin C 0.017 12.8 9.59 0.78 0.89 0.20 1.00 0.10 margin D 0.018 13.5 10.50 1.98 1.21 1.00 0.59 0.85 margin E 0.019 12.2 10.14 1.10 0.78 0.69 0.78 1.0 margin
[0035] Table 2. Tensile properties, hardness, impact toughness and corrosion resistance of Example 1.
[0036]
[0037] Embodiment 2.
[0038] A 50kg steel ingot was melted in a vacuum induction furnace, and the steel composition was set according to the component B in Table 1. Pure Fe, pure Ni, pure copper, ferrochrome, ferromolybdenum, ferroniobium, titanium aluminum alloy, etc. were mixed and filled into a crucible, heated until completely melted and cast; the ingot was cast after vacuum consumable remelting; the billet was kept at 1100℃ for 10 hours for homogenization; then forged, the forging ratio was 5, and the final forging temperature was 850℃; the forging was kept at 850℃ for 2 hours, then furnace cooled to 500℃ and unloaded, and asbestos coated. After pickling, the forging was heated to 900℃ with the furnace and kept for 2 hours, then quickly heated to 1050℃ and kept for 2 hours, then oil cooled, and cold rolled at 300℃ for five times, with a total reduction of 15%; then kept at -80℃ to -196℃ for 4 hours and returned to room temperature, and finally kept at 450℃ for 7 hours and air cooled, and aged for 3 times. The final properties are shown in Table 3. Figure 2 The microstructure and microscopic features of the martensite matrix of the sample after aging at -130°C cryogenic treatment in Example 2.
[0039] Table 3. Tensile properties, hardness, impact toughness and corrosion resistance of Example 2.
[0040]
[0041] Embodiment three.
[0042] A 50kg steel ingot is melted in a vacuum induction furnace, and the steel composition is set according to the component C in Table 1. Pure Fe, pure Ni, pure copper, ferrochrome, ferromolybdenum, ferroniobium, titanium aluminum alloy, etc. are mixed and filled into a crucible, heated until completely melted and cast; the ingot is cast after vacuum electroslag remelting; the billet is kept at 1150℃ for 8h for homogenization; then forged, the forging ratio is 8, and the final forging temperature is 900℃; the forging is kept at 900℃ for 2h and then cooled to 500℃ and taken out of the furnace, and asbestos coated. After pickling, the forging is heated to 950℃ with the furnace and kept for 2h, then quickly heated to 1100℃ and kept for 2h, then oil-cooled, and cold rolled five times at 200℃, with a total reduction rate of 10%; then kept at -130℃ for 4h and returned to room temperature, finally kept at 350℃~500℃ for 6h and air-cooled, and aging treated twice. The final performance is shown in Table 4.
[0043] Table 4. Tensile properties, hardness, impact toughness and corrosion resistance of Example 3.
[0044]
[0045] According to Table 4, when the aging temperature is within 350℃~500℃, the yield strength of the steel of the present invention can exceed 1800MPa, and the tensile strength exceeds 1900MPa, while in the comparative example, when the temperature is 300℃ or 600℃, the yield strength does not exceed 1700MPa, and the tensile strength does not exceed 1800MPa, and the elongation and plastic toughness are significantly reduced. It can be seen that the present invention obtains high strength plasticity and corrosion resistance through reasonable alloy design with appropriate heat treatment process, and through matching the nano-sized precipitate phase with martensite characteristics.
[0046] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength, high-toughness, corrosion-resistant martensitic aging stainless steel, characterized in that: The chemical composition mass percentage of high-strength, high-toughness, corrosion-resistant martensitic aging stainless steel is: Cr: 11.0%-13.5%, Ni: 9.5%~10.5%, Mo: 0.5%-2.0%, Al: 0.2%~1%, Ti: 0.5%~1.0%, Nb: 0.2%~1.0%, Cu: 0.1%~1.0%, Mn: ≤0.20%, P: ≤0.01%, S: ≤0.01%, Si: ≤0.20%, O: ≤0.01%, C: ≤0.02%, and the balance is Fe.
2. The high-strength, high-toughness, corrosion-resistant martensitic aging stainless steel according to claim 1, characterized in that The microstructure of the high-strength, high-toughness, corrosion-resistant martensitic aged stainless steel is a matrix composed of fine lath martensite, 5%-10% lamellar residual austenite and film-like reversed austenite, and high-density nano-sized Ni3Ti, Ni3Al, Ni3Nb precipitation phases and Cu and Mo clusters are dispersed on the matrix.
3. A method for preparing high-strength, high-toughness, corrosion-resistant martensitic aging stainless steel, characterized in that: The following steps are involved: Step 1, pure Fe, pure Ni, pure copper, ferrochrome, ferromolybdenum, ferroniobium, and titanium-aluminum alloy are selected and mixed, and then filled into a crucible of a vacuum induction furnace, and heated until completely melted for casting; then the ingot is remelted by vacuum consumable melting or vacuum electroslag remelting before casting; Step 2, the ingot is kept at 1100℃~1200℃ for 5h-10h for homogenization treatment and then forged, the forging ratio is 5-9, and the final forging temperature is 850℃~950℃; after forging, it is kept at 850℃~950℃ for 1~2h and then cooled to 400~500℃ and taken out of the furnace. After being taken out of the furnace, the ingot is asbestos coated or buried in sand for slow cooling; Step 3, the forging is kept at 850°C to 1000°C, then quickly heated to 1050°C to 1150°C, kept for 0.5h to 2h, and then oil-cooled, and then rolled at 20°C to 300°C by 5% to 15%, with a single-pass reduction rate of ≤5%; Step 4, the rolled piece is kept at -80°C to -196°C for 2h-4h and then restored to room temperature, and finally kept at 350°C to 500°C for 6h-18h and then air-cooled, and aged for 2-3 times to obtain high-strength, high-toughness, corrosion-resistant martensitic aged stainless steel.
Citation Information
Cited By
1700MPa-grade maraging stainless steel plate resistant to deep-sea high-pressure abrasion and manufacturing method of 1700MPa-grade maraging stainless steel plate
CN121826522A
Ultrahigh-strength corrosion-resistant maraging stainless steel as well as preparation method and application thereof
CN122147186A
